Comparison of lipid profile values in pediatric patients with cyanotic and acyanotic congenital heart disease - Fifi Febria Ningsih; Hafaz Zakky Abdillah; Selvi Nafianti (Paediatrica Indonesiana, 2022)
Background Incidence of congenital heart disease (CHD) is about 0.8% of every child born. This heart defect is associated with dyslipidemia in children. Lipid profiles examination in patients with CHD can be used to determine risk factors for atherosclerosis. Objective To examine differences in lipid profiles in children with cyanotic and acyanotic CHD. Methods This was a cross-sectional study on 60 pediatric CHD patients at Haji Adam Malik Hospital, Medan, North Sumatera, from December 2020 to March 2021. Subjects were included by consecutive sampling. Data of patient’s age, gender, weight, height, complete blood count, blood glucose, and lipid profiles were recorded. Unpaired T-test analysis and Mann-Whitney test were then performed to analyze variables in cyanotic and acyanotic CHD patients. Results Of a total of 60 CHD children, 26 subjects had a diagnosis of cyanotic CHD and 34 subjects had a diagnosis of acyanotic CHD. The most common cause of cyanotic CHD was tetralogy of Fallot (76.9%), while the most common cause of acyanotic CHD were ventricular septal defect and patent ductus arteriosus (32.4% each). Analysis of lipid profiles on both groups revealed that low density lipoprotein (LDL) was significantly lower in the cyanotic group than in the acyanotic group (P<0.05). However, other lipid profile values, were not significantly different between groups. In addition, there was no significant difference in incidence of dyslipidemia between cyanotic and acyanotic CHD. Conclusion Low density lipoprotein is significantly lower in the cyanotic CHD group than in the acyanotic CHD group. But there are no significant differences in the other lipid profiles measurement and incidence of dyslipidemia between groups.